Molecular cloning of seal myoglobin mRNA. - Wood, D (1982)
Grey seal skeletal muscle containing high levels of myoglobin was used to prepare poly(A)+ RNA. In vitro translation of this RNA produced a range of polypeptides including myoglobin. cDNA was prepared by reverse transcription of muscle poly(A)+ RNA and cloned into the plasmid pAT 153. 4% of cDNA recombinants were shown to contain myoglobin cDNA inserts. DNA sequence analysis of one clone (pSM 178) which contained a relatively large myoglobin cDNA insert showed an incomplete cDNA comprising the terminal 293 nucleotides of 3' non-translated mRNA sequences. Hybridization experiments using this myoglobin cDNA indicated that seal myoglobin is coded by a single gene which is transcribed to give a 1400 nucleotide mRNA considerably longer than related haemoglobin mRNAs.